The Influence of Coolant Fluid Variations on the Thermoelectric Generator Performance Utilizing Solar Radiation on Zinc Roof - Khairul Rezki; Primawati Primawati; Ambiyar Ambiyar; Remon Lapisa (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Solar energy can be converted into electricity through a thermoelectric generator that operates based on the Seebeck effect, where a greater temperature difference in the thermoelectric element produces a higher voltage. This research aims to evaluate the performance of a thermoelectric generator with various coolant fluids. The study utilized a prototype house with a corrugated zinc roof. Eight thermoelectric generators of SP 1848 27145 SA type, connected in series, were installed beneath the zinc roof. Data were collected over three days from 08:00 to 16:00 in an area exposed to direct sunlight. The results showed an average voltage of 0.593 V for air cooling, 0.539 V for water coolant, and 0.639 V for liquid cooling. From the data, the highest voltage achieved was 1.013 V with liquid cooling, indicating that liquid cooling provides superior cooling capability. Energi surya dapat diubah menjadi listrik melalui termoelektrik generator yang bekerja berdasarkan efek Seebeck, di mana perbedaan temperatur yang lebih besar termoelektrik akan menghasilkan tegangan yang lebih besar. Penelitian ini bertujuan untuk mengevaluasi kinerja termoelektrik generator dengan berbagai jenis cairan pendingin. Penelitian ini menggunakan prototipe rumah dengan atap seng bergelombang. Delapan termoelektrik generator tipe SP 1848 27145 SA yang terhubung seri akan dipasang di bawah atap seng. Data dikumpulkan selama tiga hari pada jam 08.00 - 16.00 di area yang terkena sinar matahari langsung. Hasilnya, rata-rata tegangan yang dihasilkan adalah 0,593 V untuk pendingin udara, 0,539 V untuk pendingin water coolant, dan 0,639 V untuk pendingin air. Dari data tersebut, tegangan tertinggi yang dicapai adalah 1,013 V dengan pendingin air. Hal ini menunjukkan bahwa pendingin air memiliki kemampuan pendinginan yang lebih baik.